Economic consequences of geotechnical instabilities in open cut coal mines - Young, K; Robotham, A; Virk, G (Slope Stability 2020: 2020 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2020)
Having a robust reporting culture and a best practice reporting and recording tool has enabled BHP Coal to record and manage over 9,000 geotechnical hazards in their open cut mines over the past 12 years. The good reporting culture and well-defined trigger action response plan (TARP) process indicates that the majority are TARP level 1 hazards, which only require additional monitoring or standoffs. However, some of these hazards have had a significant financial impact on the business. Quantifying the direct and indirect economic consequences of geotechnical hazards on the business is critical to inform appropriate exploration and mine planning decisions. The costing process is complex, particularly regarding the impacts on productivity such as re-scheduling equipment, and temporarily moving to less economic pits. The geotechnical hazards recorded at BHP’s coal mines over two years were costed using a BHP Coal developed tool. Costing included consequences incurred by the business due to geotechnical issues, such as the cost of lost, delayed and diluted coal, equipment remediation and re-scheduling, and delays to the mining schedule. Investigations into the relationship between the root cause and hazard cost identified geological structure, unachievable design, material strength, and blasting as major contributing factors. Results indicate that productivity for the business is most sensitive to hazards that result in delayed or abandoned coal. Unrecognised geological structures in the highwall were assessed to have the largest economic consequence at BHP coal mines over the two years, driven by lost coal, delayed coal, diluted coal, and buttressing of highwalls to provide additional stability.
Keywords: geotechnical instabilities; economic consequences; coal mines; cost